PROCESS IN THE HYDROTHERMALLY ALTERED AREA AT SOUTHERN MOUNTAIN OF LOMBOK ISLAND, INDONESIA - dwi winarti; Srijono Srijono (KURVATEK, 2016)
Landslide disasters are abundant in the mountainous areas of Lombok Island, Indonesia. Most landslides frequently occur in areas intensively suffered by hydrothermal alteration including Pelangan Village at Southern Mountain, West Lombok Regency. The objective of this study are to identify the most important factors controlling landslide and also to analyze the landslide susceptibility zones in the hydrothermally altered area. For this purpose, it is necessary to prepare the landslide investigation and landslide susceptibility map. In this study, the AnalyticalHierarchyProcess (AHP) is used to develop landslide susceptibility map. The landslide susceptibility was analyzed by applying weighting and scoring on each factor controlling the landslide occurrence, such as hydrothermal alteration, slope inclination, distance to lineament, and landuse.The result shows that hydrothermal alteration and slope inclination are the most important parameters to landslide occurence (39.35%), and the least important factor are distance to lineament (13.76%), and landuse (7.54%). The high susceptible zones (HS) cover about 34.20% of the total study area. The moderate susceptible zones (MS) cover about 18.40% of the total area, while about 27.80% of the total study area were classified as being the low susceptible zone (LS), and about 19.60% of the total study area are  classified as very low susceptible zone (VLS).